'In den beginne was het woord'. De vroege groei van 'parlementen' in de middeleeuwse vorstendommen der Nederlanden - M. Boone (BMGN: Low Countries Historical Review, 2005)
In the beginning, there was the word. The early evolution of parliament in the mediaeval princedoms of the Netherlands